2016
DOI: 10.1111/cei.12832
|View full text |Cite
|
Sign up to set email alerts
|

Kawasaki disease: a matter of innate immunity

Abstract: SummaryKawasaki disease (KD) is an acute systemic vasculitis of childhood that does not have a known cause or aetiology. The epidemiological features (existence of epidemics, community outbreaks and seasonality), unique age distribution and clinical symptoms and signs of KD suggest that the disease is caused by one or more infectious environmental triggers. However, KD is not transmitted person-to-person and does not occur in clusters within households, schools or nurseries. KD is a self-limited illness that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
127
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(130 citation statements)
references
References 92 publications
(147 reference statements)
2
127
0
1
Order By: Relevance
“…PAMPs and MAMPs are recognized by a type of cellular or soluble receptors, which are designated pattern recognition receptors (PRRs) (e.g., TLRs) to trigger innate immune responses, including the production of inflammatory cytokines through intracellular signaling pathways. A possible implication of these PAMPs or MAMPs in KD has been demonstrated in mouse models and more recently in clinical specimens from KD patients (78,79).…”
Section: Insight From Experimental Studies With Animal Model For Kdmentioning
confidence: 95%
“…PAMPs and MAMPs are recognized by a type of cellular or soluble receptors, which are designated pattern recognition receptors (PRRs) (e.g., TLRs) to trigger innate immune responses, including the production of inflammatory cytokines through intracellular signaling pathways. A possible implication of these PAMPs or MAMPs in KD has been demonstrated in mouse models and more recently in clinical specimens from KD patients (78,79).…”
Section: Insight From Experimental Studies With Animal Model For Kdmentioning
confidence: 95%
“…It was proposed by Lee et al that the immunopathogenesis of KD is based on a "protein homeostasis system" that controls the pathogenic toxic proteins which spread and bind to endothelial cells of coronary arteries, with the involvement of non-specific T cells and non-specific antibodies to produce various cytokines contributing to endothelial cell injury (Lee et al, 2012a). While both the innate and acquired systems are activated after pathogen infection, clinical and laboratory studies have found that the occurrence of KD is related to the activation of the innate immune system (Hara et al, 2016). Lori Broderick et al reported 4 cases of KD with the reoccurrence of inflammatory clinical symptoms similar to those in "recurrent fever syndrome" existed in febrile disease due to the dysregulation of innate immune system (Broderick et al, 2011).…”
Section: Immunopathogenesis Of Kdmentioning
confidence: 99%
“…It is noteworthy that the innate immune system has an important role during the acute phase of KD . There are some complement‐related proteins such as C3, C4 and complement factor H (CFH), overlapped.…”
Section: Evs Proteomics In Cardiovascular Diseasementioning
confidence: 99%